Totally endoscopic aortic valve replacement: Techniques and early results - Gu, Wenda; Zhou, Kan; Wang, Zhenzhong; Zang, Xin; Guo, Haijiang; Gao, Qiang; Teng, Yun; Liu, Jian; He, Biaochuan; Guo, Huiming; Huang, Huanlei (Frontiers in Cardiovascular Medicine, 2023)
Objective To demonstrate the technical details of total endoscopic aortic valve replacement using a standard prosthesis, compare the clinical effect and safety of endoscopic aortic valve replacement and traditional aortic valve replacement. Methods From 2020 to 2021, 60 consecutive patients underwent elective isolated aortic valve replacement (AVR). They were divided into two groups: the total endoscopic AVR group (TE-AVR group, 29 patients, nine women, aged 51.65±11.79 years), and the traditional full-sternotomy group (AVR group, 31 patients, 13 women, aged 54.23 ±12.06 years). Three working ports were adopted in the TE-AVR procedure. Results No patient died in either group. The cardiopulmonary bypass (CPB) time and aortic cross-clamp (ACC) time in the TE-AVR group were longer than those in the AVR group (CPB time: 177.6 ±43.2 min vs. 112.1 ± 18.1 min, p<0.001; ACC time: 118.3 ± 29.7 min vs. 67.0 ± 13.2 min, p<0.001). However, the mechanical ventilation duration (14.2 ± 9.3 hours vs. 24.0 ± 18.9 hours, p= 0.015) and postoperative hospital stay (6.0 ± 1.7 days vs. 8.0 ± 4.5 days, p= 0.025) were shorter in patients of TE-AVR group than those of AVR group. Although the ICU stay (55.1 ± 26.9 hours vs. 61.5 ± 44.8 hours, p= 0.509) and post-operative chest drainage of the first 24 hours (229.8 ± 125.0ml vs. 273.2 ± 103.2ml, p=0.146) revealed no statistical difference, there was a decreasing trend in the TE-AVR group. Among the patients of the TE-AVR group, two patients were converted to thoracotomy because of mild to moderate paravalvular leakage identified by intraoperative transesophageal echocardiography. Conclusion: Total endoscopic aortic valve replacement is safe and feasible, with less trauma and quicker recovery.